2013
DOI: 10.1186/1757-4749-5-24
|View full text |Cite|
|
Sign up to set email alerts
|

The pathogenic intestinal spirochaete Brachyspira pilosicoli forms a diverse recombinant species demonstrating some local clustering of related strains and potential for zoonotic spread

Abstract: BackgroundBrachyspira pilosicoli is an anaerobic spirochaete that can colonizes the large intestine of many host species. Infection is particularly problematic in pigs and adult poultry, causing colitis and diarrhea, but it is also known to result in clinical problems in human beings. Despite the economic importance of the spirochaete as an animal pathogen, and its potential as a zoonotic agent, it has not received extensive study.MethodsA multilocus sequence typing (MLST) method based on the scheme used for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…It is interesting to note that although B. intermedia and particularly B. pilosicoli have a similar number of STs as they have AATs (23, 24), B. hyodysenteriae shows a lower number of AATs compared to STs (5). It is thought that the high plasticity, recombination, and genetic diversity of B. pilosicoli may contribute to its ability to infect and cause disease in multiple host species, including swine, chicken, and human beings (23). This is in contrast to B. hyodysenteriae that shows a strong clonal distribution in a diverse population and is known to cause disease most often in swine (5).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is interesting to note that although B. intermedia and particularly B. pilosicoli have a similar number of STs as they have AATs (23, 24), B. hyodysenteriae shows a lower number of AATs compared to STs (5). It is thought that the high plasticity, recombination, and genetic diversity of B. pilosicoli may contribute to its ability to infect and cause disease in multiple host species, including swine, chicken, and human beings (23). This is in contrast to B. hyodysenteriae that shows a strong clonal distribution in a diverse population and is known to cause disease most often in swine (5).…”
Section: Discussionmentioning
confidence: 76%
“…Multilocus sequence typing (MLST) is a high-resolution method that uses nucleotide sequence differences between conserved housekeeping genes to characterize and differentiate genotypes of a pathogen (19). This technique has been used for local and global molecular epidemiological studies of various Brachyspira species (20), including B. hyodysenteriae (5,21,22), Brachyspira pilosicoli (23), Brachyspira intermedia (24), Brachyspira murdochii, and Brachyspira innocens (25), thus warranting its application for the characterization of B. hampsonii.…”
mentioning
confidence: 99%
“…1 and 2). Furthermore, B. pilosicoli, which is known to be a highly recombinant species that demonstrates a substantial amount of genomic variation (40), could be prone to developing mutations associated with antimicrobial resistance. The tendency of B. pilosicoli to develop resistance more rapidly than other Brachyspira species is supported by the "skipped well" phenomenon, i.e., spontaneous mutations associated with in vitro resistance to an antimicrobial that develops in the inoculated medium during susceptibility testing (36).…”
Section: Discussionmentioning
confidence: 99%
“…The spirochaete has a recombinant population structure (Trott et al, 1998;Neo et al, 2013), and genomic sequencing has revealed that strains show extensive genomic rearrangements and that their genome sizes vary (Wanchanthuek et al, 2010;Mappley et al, 2012;Lin et al, 2013). Infection with B. pilosicoli occurs commonly in intensively housed pigs and adult poultry, and also in human beings living in crowded conditions in developing countries (Trott et al, 1997;Mikosza & Hampson, 2001;Margawani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%